Analisis Penerapan Lean Management Dalam Operasional PT KAI Untuk Mengurangi Pemborosan dan Meningkatkan Produktivitas - Tri Ngudi Wiyatno; Panji (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2025)
This study aims to analyze the implementation of Lean Management in the operations of PT Kereta Api Indonesia (PT KAI) to reduce waste and increase productivity. Lean Management is an approach that focuses on eliminating activities that do not provide added value, thereby increasing efficiency and service quality. The research method used is a descriptive qualitative approach with a case study design. Data were obtained through in-depth interviews, direct observation, and analysis of documents related to PT KAI's operations. The results of the study indicate that the main waste in PT KAI's operations includes long waiting times, inefficient processes, and excessive use of resources. With the implementation of Lean Management, PT KAI is able to identify the causes of waste and implement corrective measures, such as optimizing travel schedules, improving workflows, and utilizing digital technology. As a result, operational efficiency increased by up to 25%, waiting times were significantly reduced, and customer satisfaction increased. This study provides strategic recommendations for PT KAI in integrating Lean Management as part of the organizational culture to achieve operational sustainability.